Barbados : Report on Observance of Standards and Codes; Fiscal Transparency Module. (IMF Staff Country Reports; Country Report ;, 2007)
This Report on the Observance of Standards and Codes assesses Fiscal Transparency for Barbados. The report reveals that Barbados has a number of good practices on fiscal transparency including a legal requirement to publish the budget Estimates, the annual report of the accountant general, and the annual Report of the auditor general as well as websites that provide data on budget outturn for current and previous years. The outturn prior to the budget year is provided alongside budget estimates, which are provided on a gross basis according to administrative, economic, program, and functional classifications.